Experimental diabetes mellitus exacerbates ischemia/reperfusion-induced myocardial injury by promoting mitochondrial fission: Role of down-regulation of myocardial Sirt1 and subsequent Akt/Drp1 interaction. (December 2018) - Tao, Aibin; Xu, Xuemei; Kvietys, Peter; Kao, Raymond; Martin, Claudio; Rui, Tao
Graphical abstract: Highlights: Diabetes Mellitus results in down-regulation of myocardial Sirt1. Reduced Sirt1 in cardiomyocytes decreases Akt phosphorylation that increases Drp1 activation after ischemia/reperfusion. Increased Drp1 activation induces mitochondrial fission, oxidant stress and exaggerates ischemia/reperfusion-induced myocardial injury. Abstract: Diabetes mellitus (DM) has a negative impact on clinical outcomes for patients with myocardial infarction. The aim of the present study was to assess whether decreased myocardial levels of Sirtuin1 (Sirt1) contribute to the increased susceptibility of the diabetic myocardium to ischemia/reperfusion (I/R) injury. In vivo, myocardial levels of Sirt1 expression and activity were decreased in mice with STZ-induced DM. Increasing Sirt1 activity prevented the DM-induced exacerbation of myocardial mitochondrial fission, apoptosis and dysfunction elicited by I/R. In vitro, anoxia/reoxygenation (A/R) challenge of cardiomyocytes (CM) that were preconditioned with high glucose (HG-CM) resulted in an exacerbation of the A/R-induced mitochondrial fission, oxidant production and CM apoptosis; effects reversed by increasing Sirt1 protein/activity. Inhibition of Drp1 prevented the exacerbated CM mitochondrial fission and oxidant production after A/R challenge of HG-CM. Decreased Sirt1 in HG-CM was associated with decreased Akt phosphorylation. Inhibition of Akt had no effect on CM Sirt1 levels, but further increased Drp1 activation. Increasing Sirt1 levels prevented the decrease in Akt phosphorylation and Drp1 activation in A/R challenged HG-CM. In conclusion: our data indicate that the increased vulnerability of the diabetic myocardium to I/R-induced apoptosis/dysfunction is attributable, in part, to decreased myocardial Sirt1 activity which leads to a decrease in Akt activation, an increase in Drp1 activity, culminating in excessive mitochondrial fission and ROS production.